The Critical Role of IL-15–PI3K–mTOR Pathway in Natural Killer Cell Effector Functions - Nandagopal, Neethi; Ali, Alaa Kassim; Komal, Amandeep Kaur; Lee, Seung-Hwan (Frontiers in Immunology, 2014)
Natural killer (NK) cells were so named for their uniqueness in killing certain tumor and virus-infected cells without prior sensitization. Their functions are modulated in vivo by several soluble immune mediators; IL-15 being the most potent among them in enabling NK cell homeostasis, maturation and activation. During microbial infections, NK cells stimulated with IL-15 display enhanced cytokine responses. This priming effect has previously been shown with respect to increased IFN-γ production in NK cells upon IL-12 and IL-15/IL-2 co-stimulation. In this study, we explored if this effect of IL-15 priming can be extended to various other cytokines and observed enhanced NK cell responses to stimulation with IL-4, IL-21, IFN-α and IL-2 in addition to IL-12. Notably, we also observed elevated IFN-γ production in primed NK cells upon stimulation through the Ly49H activation receptor. Currently, the fundamental processes required for priming and whether these signaling pathways work collaboratively or independently for NK cell functions are poorly understood. To identify the key signaling events for NK cell priming, we examined IL-15 effects on NK cells in which the pathways emanating from IL-15 receptor activation were blocked with specific inhibitors. Our results demonstrate that the PI3K-AKT-mTOR pathway is critical for cytokine responses in IL-15 primed NK cells. Furthermore, this pathway is also implicated in a broad range of IL-15 induced NK cell effector functions such as proliferation and cytotoxicity. Likewise, NK cells from mice treated with rapamycin to block the mTOR pathway displayed defects in proliferation, IFN-γ and granzyme B productions resulting in elevated viral burdens upon MCMV infection. Taken together, our data demonstrates the requirement of PI3K-mTOR pathway for enhanced NK cell functions by IL-15, thereby coupling the metabolic sensor mTOR to NK cell anti-viral responses.